Evaluation and comparison of tooth size discrepancies among different malocclusion groups - Mujagić, A.; Džemidžić, V.; Tiro, A.; Nakaš, E. (Dentitio, 2016)
Introduction: The compliance of proportions between the mesiodistal dimensions of the upper and the lower teeth is necessary for good intercuspidation. Given that a significant discrepancy in tooth size can prevent ideal occlusion at the end of orthodontic treatment, the absence of tooth size discrepancy is a significant factor for the realization of the ideal occlusion. Aim: Aim of this study was to determine whether there is a difference in the incidence of tooth size discrepancies among different skeletal malocclusion groups in the orthodontic patients. Material and methods: The sample comprised 300 pretreatment study casts (118 males and 182 females) with fully erupted and complete permanent dentition except third molars, which were selected randomly from records of orthodontic patients. All subjects were divided in three groups, according to the Angle classification of malocclusion. The measurements were made on study models with digital calipers accurately to 0.01 mm. The Class was defined by using the Steiner analysis on lateral cephalograms. The subjects were divided into three groups depending on the value of the ANB angle. For every subject, the value of the angles SNA, SNB and ANB was measured. The reliability of measurements was examined by the Pearson's correlation coefficient. To determine whether there were gender differences an independent sample t-test was performed. Results: There is no statistically significant differences in Bolton's discrepancy by different gender, or at different classes. The average value of the anterior Bolton ratio was 78.16 and of the overall were 90.87. Values of the anterior and overall Bolton ratios are highest in patients with Class III. The highest average value of anterior discrepancy was in male subjects with III Class (-0.72), while the highest average value of overall discrepancy was in male subjects with II Class (0.65). Conclusion: The results of the study show that there are no statistically significant differences in Bolton's discrepancy by different gender, or at different classes.